Ambiguous Narratives of World War Technologies in Contemporary Military History Museums. Issue 1 (1st March 2022) - Jaeger, Stephan
Abstract: This article provides an analysis of how military history museums in Germany, Britain, Belgium, Poland, and the United States exhibit and contextualize weapon technologies that were developed in the two world wars. The article focuses on technologies (gas warfare, the atomic bomb, tanks, and the V2 long-range rocket) that are directly connected to military success and innovation but also relate to dehumanization and destruction. By employing the analytical concepts of experientiality and of antagonistic, cosmopolitan, and entangled memory, this article demonstrates how museums can create open or closed narratives, steer the visitor toward particular interpretations, enhance or deconstruct the authentic aura of technological artifacts, and stage the symbolic potential of technologies. In addition, it shows how museums can educate visitors and allow them to experience the ambiguities, controversies, and complexities of these technologies.